Cell derived matrices from bovine corneal endothelial cells as a model to study cellular dysfunction. (January 2023) - Jalilian, Iman; Muppala, Santoshi; Ali, Maryam; Anderson, Johnathon D.; Phinney, Brett; Salemi, Michelle; Wilmarth, Phillip A.; Murphy, Christopher J.; Thomasy, Sara M.; Raghunathan, VijayKrishna
Abstract: Purpose: Fuchs endothelial corneal dystrophy (FECD) is a progressive corneal disease that impacts the structure and stiffness of the Descemet's membrane (DM), the substratum for corneal endothelial cells (CECs). These structural alterations of the DM could contribute to the loss of the CECs resulting in corneal edema and blindness. Oxidative stress and transforming growth factor-β (TGF-β) pathways have been implicated in endothelial cell loss and endothelial to mesenchymal transition of CECs in FECD. Ascorbic acid (AA) is found at high concentrations in FECD and its impact on CEC survival has been investigated. However, how TGF-β and AA effect the composition and rigidity of the CEC's matrix remains unknown. Methods: In this study, we investigated the effect of AA, TGF-β1 and TGF-β3 on the deposition, ultrastructure, stiffness, and composition of the extracellular matrix (ECM) secreted by primary bovine corneal endothelial cells (BCECs). Results: Immunofluorescence and electron microscopy post-decellularization demonstrated a robust deposition and distinct structure of ECM in response to treatments. AFM measurements showed that the modulus of the matrix in BCECs treated with TGF-β1 and TGF-β3 was significantly lower than the controls. There was no difference in the stiffness of the matrix between the AA-treated cell and controls. Gene Ontology analysis of the proteomics results revealed that AA modulates the oxidative stress pathway in the matrix while TGF-β induces the expression of matrix proteins collagen IV, laminin, and lysyl oxidase homolog 1. Conclusions: Molecular pathways identified in this study demonstrate the differential role of soluble factors in the pathogenesis of FECD. Highlights: Bovine corneal endothelial cells deposit a matrix while maintaining cellular morphology. Matrix deposited after TGFβ treatment are softer akin to human FECD. Cell derived matrices may model cell-matrix interactions for FECD biology.